2024
DOI: 10.1001/jamainternmed.2024.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nirmatrelvir-Ritonavir and Symptoms in Adults With Postacute Sequelae of SARS-CoV-2 Infection

Linda N. Geng,
Hector Bonilla,
Haley Hedlin
et al.

Abstract: ImportanceThere is an urgent need to identify treatments for postacute sequelae of SARS-CoV-2 infection (PASC).ObjectiveTo assess the efficacy of a 15-day course of nirmatrelvir-ritonavir in reducing the severity of select PASC symptoms.Design, Setting, and ParticipantsThis was a 15-week blinded, placebo-controlled, randomized clinical trial conducted from November 2022 to September 2023 at Stanford University (California). The participants were adults with moderate to severe PASC symptoms of 3 months or longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…It is important to consider that this study, in agreement with our study, also found that the effects of antivirals were more pronounced for some specific post-COVID symptoms such as fatigue, muscle pain, or dyspnea [ 30 ]. The STOP-PASC Randomized Clinical Trial has recently observed that oral administration of Nirmatrelvir-Ritonavir in COVID-19 survivors with post-COVID symptoms did not show a significant benefit to their symptoms [ 31 ]. Similarly, the effects of Nirmatrelvir-Ritonavir on post-COVID sequalae are also controversial since Wang et al [ 32 ] found a decrease in the long-term risk of death and the development of post-acute cardiovascular and respiratory sequelae in a large sample of inpatient COVID-19 survivors, whereas Ioannou et al [ 33 ] did not find this protective effect in a sample of non-hospitalized veterans.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that this study, in agreement with our study, also found that the effects of antivirals were more pronounced for some specific post-COVID symptoms such as fatigue, muscle pain, or dyspnea [ 30 ]. The STOP-PASC Randomized Clinical Trial has recently observed that oral administration of Nirmatrelvir-Ritonavir in COVID-19 survivors with post-COVID symptoms did not show a significant benefit to their symptoms [ 31 ]. Similarly, the effects of Nirmatrelvir-Ritonavir on post-COVID sequalae are also controversial since Wang et al [ 32 ] found a decrease in the long-term risk of death and the development of post-acute cardiovascular and respiratory sequelae in a large sample of inpatient COVID-19 survivors, whereas Ioannou et al [ 33 ] did not find this protective effect in a sample of non-hospitalized veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, surveys did not include the number of past infections per respondent, information on anti-viral medication, or when the worst symptomatic infection occurred in relation to the most prevalent virus variant. If available, data on participants’ use of antiviral treatments (i.e., nirmatrelvir) would likely have a greater impact on our symptom-severity analysis, as research on the effectiveness of antiviral drugs for preventing long COVID has been mixed [ 40 , 41 , 42 ]. An increase in the number of times a patient has had a COVID infection is associated with an increase in the likelihood of experiencing long-term symptoms, thus participant reinfection statistics are more likely to influence our long-COVID analysis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Stanford University's STOP-PASC trial, which included 155 participants, Paxlovid did not show significant benefit in improving extant fatigue, brain fog, body aches, cardiovascular symptoms, shortness of breath, or gastrointestinal symptoms. 13 In addition to treating PASC, researchers have begun to explore whether Paxlovid treatment in the acute phase of COVID-19 infection could help prevent the onset of PASC. One plausible pathway could be reducing infection severity.…”
Section: Introductionmentioning
confidence: 99%